A New Approach to the Synthesis of 1-Arylbenzimidazole-2-thiones from Nitroarenes and Anilines through Halogen-Free Substitution of Hydrogen via Iminophosphorane Intermediates - Łukasik, Emilia; Wróbel, Zbigniew (Synthesis, 2016)
2-(Arylamino)phenyliminophosphoranes, formed directly from 2-nitrosodiarylamines, undergo a high-yielding cyclocondensation with CS2, providing a variety of 1-arylbenzimidazole-2-thiones. The reaction concludes a new synthetic route leading to the title compounds from simple nitroarenes and arylamines. The protocol is superior to common methods that use N-arylarylenediamines because it omits the SNAr substitution of halogen atoms in ortho-halonitroarenes, as well as reduction processes required for the synthesis of the intermediate diamines.
Keywords: annulation; nitrogen heterocycles; cyclization; nitroso compounds; fused-ring systems